Virtual Mentoring as a potential pathway to increase retention of historically underrepresented minority students in the Geosciences - Marasco, Leslie (2019)
Mentoring365 is a virtual mentoring program developed by the American Geophysical Union, in collaboration with other geoscience associations including the American Meteorological Society, the Association for Women Geoscientists, Incorporated Research Institutions for Seismology, and the Society of Exploration Geophysicists. Participant data of the Mentoring365 program was evaluated to identify demographic patterns and the potential of virtual mentoring as a pathway to increase retention of URM students in the geosciences. As of 24 June 2019, 514 total applicants have applied and been accepted into the Mentoring365 program, comprising 173 mentors and 364 mentees (some participants serve in both roles). Participants represent 56 countries spanning 6 continents. 60.4% of mentees and 33.5% of mentors identify as non-white. 48.6% of mentees and 47.7% of mentors identify as female. To date, Mentoring365 has facilitated 159 mentoring connections within the program. Non-white mentees are twice as likely as white mentees to select a non-white mentor. Of the non-white mentees who selected a non-white mentor, 47.6% selected a mentor of their same race. Female and male mentees selected mentors that matched their gender identity at nearly equal rates, both preferring a mentor of their same gender. 62.8% male mentees selected a male mentor and 64.1% female mentees selected a female mentor. Participant data supports that URM students are looking to connect with mentors that represent them racially at higher rates than white students. Both male and female mentees prefer a mentor of their same gender identity, but there is not a significant difference in preference between genders. Cultivating inclusivity in the geosciences can assist in retaining URM students and virtual mentoring programs such as Mentoring365 can potentially be part of the effort. Mentoring365 participant data alone, however, is insufficient to evaluate the efficacy of virtual mentoring to increase retention. Longitudinal data on the retention rates and outcomes of URM students who participated in virtual mentoring programs as well as those who did not should be evaluated to gain further insights.